Bromodomain-containing protein BRPF1 is a therapeutic target for liver cancer - Carol Lai-Hung Cheng; Felice Hoi-Ching Tsang; Lai Wei; Mengnuo Chen; Don Wai-Ching Chin; Jialing Shen; Cheuk-Ting Law; Derek Lee; Carmen Chak-Lui Wong; Irene Oi-Lin Ng; Chun-Ming Wong (Communications Biology, 2021)
Cheng et al. suggest that BRPF1 plays an oncogenic role in hepatocellular carcinoma (HCC), by controlling histone acetylation in the promoter regions of E2F2 and EZH2. Its high levels are correlated with poor survival in HCC patients, and targeting it might serve as a strategy for cancer treatment.